2019
DOI: 10.1016/j.conctc.2019.100377
|View full text |Cite
|
Sign up to set email alerts
|

Impact of antiviral AV2 in the topical treatment of HPV-associated lesions of the cervix: Results of a phase III randomized placebo-controlled trial

Abstract: Background Non-surgical topical therapies have been assessed in the treatment of precancerous lesions of the cervix. Their use can offer logistical and feasibility advantages in low-resource settings. Antiviral AV2 ® is a mixture of natural essential oils (eugenol, carvone, nerolidol, geraniol) in olive oil, and has a broad spectrum anti-viral activity. In a phase II randomized controlled trial (RCT), AV2 ® proved effective in reducing the size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Results showed that there was a significant increase in HPV test negative results and reduced cervical lesion size in the intervention group compared to the control group, suggesting that a M. communis herbal suppository can speed up virus clearance and may be effective in treating HPV infection. In contrast, topical application with a mixture of natural EOs (eugenol, carvone, nerolidol, and geraniol) in olive oil given to visual inspection of the cervix with acetic-acid-positive patients showed no differences in the regression of the lesion and HPV clearance rate between the intervention and control groups [125].…”
Section: Essential Oils Clinical Trials In Cervical Cancer and Hpv In...mentioning
confidence: 80%
“…Results showed that there was a significant increase in HPV test negative results and reduced cervical lesion size in the intervention group compared to the control group, suggesting that a M. communis herbal suppository can speed up virus clearance and may be effective in treating HPV infection. In contrast, topical application with a mixture of natural EOs (eugenol, carvone, nerolidol, and geraniol) in olive oil given to visual inspection of the cervix with acetic-acid-positive patients showed no differences in the regression of the lesion and HPV clearance rate between the intervention and control groups [125].…”
Section: Essential Oils Clinical Trials In Cervical Cancer and Hpv In...mentioning
confidence: 80%
“…In a phase III clinical trial conducted in a resource-scarce environment, eugenol, a CPT1 inhibitor, as one of the ingredients of antiviral AV2, was slightly effective in inducing the regression of cervical precancerous lesions, although there was no statistically significant difference between the treatment and placebo groups. However, this lack of statistical significance may change in a later stage in a high-resource environment and by expanding the sample size ( 131 ). Research on the involvement of CPT in cervical cancer seems to have received little attention, but it may bring new insights into the treatment of CC.…”
Section: Targeting Fatty Acid Oxidationmentioning
confidence: 99%
“…The essential oils have already received FDA approval, and their antiviral effect is well documented. As per reports, antiviral 2 formulations have been shown to inhibit viral replication by degenerating HPV-induced cervical lesions. , This NCT00002445 trial primarily focuses on the safety and effectiveness of intranasal-based IM862 drug formulation in treating Kaposi’s Sarcoma/HHV-8 in AIDS Patients. Chemically, IM862 is derived as a dipeptide from L-glutamyl-L-tryptophan.…”
Section: Recent Progress On Drug Developments For Oncogenic Virusmentioning
confidence: 99%